Os impactos socioeconômicos da Ferrovia Norte Sul no distrito de Luzimangues - TO - Abreu, Maria de Jesus Coelho (Universidade Federal do Tocantins, 2018)
The development models adopted buy the national government, ruled by a neoliberal logic and based on endogenous development theory, have proven totally inefficient for the development of the majority of the Brazilian society, because they keep benefiting the processes of capital accumulation at the expense of human development. The lack of public policies which hold development strategies that can be effective to the population is one of the distinctive marks of capitalist model; and the accumulation processes are the ones which rule the dynamics of global, regional and local economy in current globalist world. Using this framework as basis, this study aims to analyze social and economic development in Luzimangues – located in the district of Porto Nacional -To, after implementing the Multi modal Area of North-South Railway. It focus especially the concepts of development in PAC, as well as their influence on Public Policies regarding infrastructure and transportation, addressed particularly to Luzimangues. Therefore, we try to comprehend the following situations: what development is happening effectively; which policies of regional development and endogenous development are within the theoretical field of current discussions; which type of economic development is taking place in Brazil, according to the Government; how railways influence in Brazilian development; and, finally, what economic influences occur due to the Multi modal Area in Luzimangues. The methodology of this study is based in different techniques, like document analysis and field research. After a theoretical and conceptual discussion about the development possibilities in Luzimangues as a result of the implementation of the Multi modal Area, we found that it was not noticeable any growth in the last ten years, even less due to the Government enterprise, North-South Railway, because most of the population still support themselves with informal labor, live in houses that have poor structure and do not have good health, education and safety conditions. We also found that the ideal development necessary for a country, state or city do not occur simply by economic growth and modernization, especially, the technological one. It is not the case to consider that they are not necessary, but it is essential, mainly, that this growth occur along with conditions to offer life quality through the delivery of good quality education, health and safety conditions, beyond creating jobs and a fare wealth distribution among inhabitants.